Eco-Efficiency Assessment at XYZ Hospital: An Analysis Using the Data Envelopment Analysis Method - Putra, Satria; Widyawati, Luluk (INOVASI, 2025)
This study evaluates the eco-efficiency of Hospital XYZ, identifying strengths and areas for improvement in resource use, waste management, and compliance with environmental policies to support sustainability efforts. A combination of Data Envelopment Analysis (DEA) and Importance-Performance Analysis (IPA) is used. DEA measures eco-efficiency quantitatively using resource inputs and economic outputs, while IPA assesses the perceived importance and performance of environmental management practices through interviews with hospital management. DEA reveals fluctuations in eco-efficiency due to factors like resource use, waste production, and occupancy rates. IPA identifies gaps in waste segregation, energy conservation, and policy compliance. Recommendations include optimizing resource use, enhancing waste management, and strengthening sustainability-focused policies and practices.